2017
DOI: 10.1126/sciadv.1602751
|View full text |Cite
|
Sign up to set email alerts
|

Arctic sea ice, Eurasia snow, and extreme winter haze in China

Abstract: Cryospheric forcing, that is, decreasing Arctic sea ice and increasing Eurasia snow, exacerbated extreme winter haze in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
205
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(212 citation statements)
references
References 42 publications
5
205
2
Order By: Relevance
“…Several extreme wintertime air pollution events in recent years covered vast areas of northern China and were all correlated to some extent with extreme weather conditions (Zou et al, 2017).…”
Section: Seasonal Patternsmentioning
confidence: 99%
“…Several extreme wintertime air pollution events in recent years covered vast areas of northern China and were all correlated to some extent with extreme weather conditions (Zou et al, 2017).…”
Section: Seasonal Patternsmentioning
confidence: 99%
“…Recently, the role of underlying climatic factors in modulating regional weather conditions in association with severe haze events has been reported and is expected to have influenced the change in the severity of haze (e.g., Niu et al, 2010;Wang et al, 2015;Cai et al, 2017;Yin and Wang, 2017;Zou et al, 2017). These climatic factors include a weakened EAWM system and the associated decreased nearsurface wind speeds (Niu et al, 2010) and increased relative humidity in the region , reduced Arctic sea ice and anomalous sea surface temperature (SST) in the subtropical western Pacific .…”
Section: Introductionmentioning
confidence: 99%
“…The observed negative trend of the EAWM during the past few decades has caused significantly reduced wind speeds over North China and subdued atmospheric transport of pollutants, and hence it has contributed to the increasing number of haze days (Niu et al, 2010;Huang et al, 2012;Li et al, 2016). The latest studies have analyzed the possible influences of anthropogenic climate change on haze occurrences (e.g., Cai et al, 2017;Yin and Wang, 2017;Zou et al, 2017). Based on historical and future climate simulations, Cai et al (2017) suggested that anthropogenic greenhouse gas emissions and the associated changes would increase the occurrences of weather conditions conducive to Beijing winter severe haze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interactions between aerosol pollution and climate change have been substantially addressed in recent publications, for example anthropogenic climate change (Cai et al, 2017), reduced Arctic sea ice Zou et al, 2017), the Tibetan Plateau warming (Xu et al, 2016), influences of ENSO events on haze frequency in eastern China , weakened East Asian winter monsoon , decadal weakening of winds and enhanced thermal stability of the lower atmosphere Chen and Wang, 2015). Dustwind interaction (Yang et al, 2017a) and upwind transport (Yang et al, 2017b) could also intensify haze events in China.…”
Section: Introductionmentioning
confidence: 99%